Exophytic Major Recurrent Aphthous Stomatitis (Fuchs Syndrome) Triggered by Pregnancy and Lactation: A Case Report - Mittal Sindhav; Bharat Chaudhary; Ronak Shah; Parth Shah (JOURNAL OF CLINICAL AND DIAGNOSTIC RESEARCH, 2026)
Fuchs syndrome, the most severe form of major Recurrent Aphthous Stomatitis (RAS), is characterised by large, deeply penetrating oral ulcers that cause significant morbidity. While its pathogenesis involves immune dysregulation, nutritional deficiency, and hormonal influences, pregnancy and lactation-associated exacerbations remain poorly documented, and atypical exophytic presentations are exceptionally rare. Hereby, the authors report the case of a 32-year-old lifelong lacto-vegetarian female, actively breastfeeding, who presented with a third episode of severe oral ulceration over 18 months each episode temporally associated with late pregnancy, early postpartum or active lactation. On this occasion, a 6 mm ulcer progressed to a 6 cm exuberant flower-like exophytic inflammatory mass covering the entire lower lip despite seven days of oral acyclovir therapy, initiated on the basis of incidental Herpes Simplex Virus Type 1-Immunoglobulin G (HSV-1 IgG) seropositivity. Negative Herpes Simplex Virus-Immunoglobulin M (HSV-IgM) and absence of vesicular lesions excluded active herpetic infection. Borderline vitamin B12 at the lower end of the reference range (234 pg/mL) and low-normal ferritin (30 ng/mL) were identified as contributory nutritional factors in a vegetarian patient with increased lactational demands. Systemic prednisolone (20 mg daily tapered over 13 days) produced dramatic clinical improvement within 72 hours and complete epithelialisation by day 21, with no recurrence at three months. The present case illustrates the diagnostic pitfall of equating isolated HSV-1 IgG positivity with active infection, highlights the role of hormonal immunomodulation in precipitating major RAS, and reinforces the primacy of systemic corticosteroids in managing severe immune-mediated oral ulceration